2020
DOI: 10.1097/hp.0000000000001285
|View full text |Cite
|
Sign up to set email alerts
|

Automated Dicentric Aberration Scoring for Triage Dose Assessment: 60Co Gamma Ray Dose-response at Different Dose Rates

Abstract: The objective of this study was to establish radiation dose-response calibration curves using automated dicentric scoring to support rapid and accurate cytogenetic triage dose-assessment. Blood was drawn from healthy human volunteers and exposed to 60Co gamma rays at several dose rates (i.e., 1.0, 0.6, and 0.1 Gy min−1). After radiation, the blood was placed for 2 h in a 37 °C incubator for repair. Blood was then cultured in complete media to which a mitogen (i.e., phytoghemagglutinin, concentration 4%) was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…A limitation of scoring systems with DCScore is that metaphase images that are poor quality are rejected and few images that are good quality are accepted for scoring. The quality of metaphase spreads is an important factor that affects DC scoring using DCScore ( 9 , 21 ). As our study utilized images generated in previous studies for validating the semi-automated scoring method, we could not adjust the image quality and used a smaller number of metaphase images in the semi-automated scoring method than in the manual scoring method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limitation of scoring systems with DCScore is that metaphase images that are poor quality are rejected and few images that are good quality are accepted for scoring. The quality of metaphase spreads is an important factor that affects DC scoring using DCScore ( 9 , 21 ). As our study utilized images generated in previous studies for validating the semi-automated scoring method, we could not adjust the image quality and used a smaller number of metaphase images in the semi-automated scoring method than in the manual scoring method.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of manual DCA has been well-studied for radiation biodosimetry ( 17 20 ), but relatively few studies have validated DCScore. In most of these studies, the performance of DCScore has been evaluated in triage using ex vivo irradiated blood ( 9 , 21 , 22 ); however, the application of DCScore in estimating the accurate radiation dose in in vivo irradiated humans has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…To accelerate the speed of DCA analysis for dose estimation, automated tools were developed. The automated tools included harvesters [Subramanian 2020], metaphase nders [Weber et al 1992 with automatic dicentric scoring was found to be close to the dose obtained with manual dicentric scoring of 500 metaphases [Vaurijoux et al 2009].…”
Section: Introductionmentioning
confidence: 54%
“…Acknowledging that the DCA is currently the best-established cytogenetic technique for absorbed radiation dose assessment, it is somewhat impractical for triage of mass casualty events owing to its labor-intensive and time-consuming procedures. While lymphocyte culture for 48 h is inevitable, many research is directed to streamline DCA processes by automating DC scoring in metaphase images using machine learning image processing techniques (36)(37)(38)(39)(40). Hence, many image training classifiers were created to improve the specificity of automated DC analysis algorithm.…”
Section: Discussionmentioning
confidence: 99%